ON THE ESTIMATION OF ELASTIC STRESSES IN THE MANTLE AT THE TIME MOMENT OF A LARGE METEORITE FALL - Molodensky S.M. (My University, 2005)
Simple relations are obtained for estimating stresses in the mantle at the time moment of a large meteorite fall from values of the velocity and mass of the meteorite and the sizes of its crater. It is shown that the fall of the Chicxulub meteorite, the largest over the last 100 Myr, produced stresses of the order of 0.1-1 MPa.
Keywords: STRESSES IN THE MANTLE; GEODYNAMICS